Using Paired Reading Method to Improve Tenth Grade Students' Reading Comprehension - Arzam, Ismail Zaid; Setiawan, Heru; Hartati, Sri (CV. Doki Course and Training, 2024)
The objective of this study was to find out whether or not there was any significant differences of the tenth graders’ reading comprehension between the students who were taught by using paired reading method and those who are not at SMA Muhammadiyah 01 Palembang. this study's sample consisted of 71 students chosen using a purposive selection approach. they were placed into two groups: experimental and control groups. this study used a quasi-experimental design. the data collection tool was reading comprehension a using paired reading method, which was administered twice to the sample (pretest and posttest). there were 30 valid multiple-choice questions. the test resulted in a two-tailed significant difference (p=0,309) above the significance level (0.05). hence, the hypothesis was accepted, signifying a noteworthy distinction in reading comprehension between students was any significant differences of the tenth graders’ reading comprehension between the students who were taught by using paired reading method and those who are not at SMA Muhammadiyah 01 Palembang, the null hypothesis (ho) was rejected and the alternative hypothesis (ha) confirmed. there was a substantial to there was any significant differences of the tenth graders’ reading comprehension between the students who were taught by using paired reading method and those who are not at SMA Muhammadiyah 01 Palembang.